An update on the anxiolytic and neuroprotective properties of etifoxine: from brain GABA modulation to a whole-body mode of action - Nuss P (Dove Medical Press, 2019)
Philippe Nuss,1,2 Florian Ferreri,1 Michel Bourin31Department of Adult Psychiatry and Medical Psychology, Sorbonne University, Saint-Antoine Hospital, Paris, France; 2Inserm UMR_S938, Saint-Antoine Research Centre, Sorbonne University, Paris, France; 3Department of Neurobiology of Anxiety and Depression, Faculty of Medicine, Nantes University, Nantes, FranceAbstract: Treating the signs and symptoms of anxiety is an everyday challenge in clinical practice. When choosing between treatment options, anxiety needs to be understood in the situational, psychiatric, and biological context in which it arises. Etifoxine, a non-benzodiazepine anxiolytic drug belonging to the benzoxazine class, is an effective treatment for anxiety in response to a stressful situation. In the present review, we focused on several aspects of the cerebral and somatic biological mechanisms involved in anxiety and investigated the extent to which etifoxine’s mode of action can explain its anxiolytic activity. Its two mechanisms of action are the modulation of GABAergic neurotransmission and neurosteroid synthesis. Recent data suggest that the molecule possesses neuroprotective, neuroplastic, and anti-inflammatory properties. Etifoxine was first shown to be an effective anxiolytic in patients in clinical studies comparing it with clobazam, sulpiride, and placebo. Randomized controlled studies have demonstrated its anxiolytic efficacy in patients with adjustment disorders (ADs) with anxiety, showing it to be superior to buspirone and comparable to lorazepam and phenazepam, with a greater number of markedly improved responders and a better therapeutic index. Etifoxine’s noninferiority to alprazolam has also been demonstrated in a comparative trial. Significantly less rebound anxiety was observed after abrupt cessation of etifoxine compared with lorazepam or alprazolam. Consistent with this finding, etifoxine appears to have a very low dependence potential. Unlike lorazepam, it has no effect on psychomotor performance, vigilance, or free recall. Severe adverse events are in general rare. Skin and subcutaneous disorders are the most frequently reported, but these generally resolve after drug cessation. Taken together, its dual mechanisms of action in anxiety and the positive data yielded by clinical trials support the use of etifoxine for treating the anxiety signs and symptoms of individuals with ADs.Keywords: etifoxine, adjustment disorders, TSPO, translocator protein 18 kDa, 3α, allopregnanolone, 5α-THP, GABA, benzodiazepines, anxiety, neuroprotection